2009
DOI: 10.1111/j.1540-8175.2008.00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Pulmonary Regurgitation

Abstract: A patient with first-degree atrioventricular (AV) block and pulmonary regurgitation underwent a transthoracic echocardiogram. Continuous wave Doppler interrogation of the pulmonic valve displayed a biphasic regurgitation pattern. A discussion of the potential mechanism underlying this pattern is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Kisanuki et al (1987) reported three cases with a late diastolic PA forward flow thought to be caused by decreased RV compliance and highly elevated RVEDP. Moukarbel et al (2009) described a case with a biphasic PR flow velocity pattern having a deep dip at the timing of the atrial contraction.…”
Section: The Reason Why the Epadp Prea Was More Accurate Than The Epamentioning
confidence: 99%
“…Kisanuki et al (1987) reported three cases with a late diastolic PA forward flow thought to be caused by decreased RV compliance and highly elevated RVEDP. Moukarbel et al (2009) described a case with a biphasic PR flow velocity pattern having a deep dip at the timing of the atrial contraction.…”
Section: The Reason Why the Epadp Prea Was More Accurate Than The Epamentioning
confidence: 99%